2009
DOI: 10.1152/ajprenal.00137.2009
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced stress induces loss of microvascular endothelial Tie2 in the kidney which is not associated with reduced glomerular barrier function

Abstract: Both hemorrhagic shock and endotoxemia induce a pronounced vascular activation in the kidney which coincides with albuminuria and glomerular barrier dysfunction. We hypothesized that changes in Tie2, a vascular restricted receptor tyrosine kinase shown to control microvascular integrity and endothelial inflammation, underlie this loss of glomerular barrier function. In healthy murine and human kidney, Tie2 is heterogeneously expressed in all microvascular beds, although to different extents. In mice subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 44 publications
(48 reference statements)
4
59
1
Order By: Relevance
“…explain the nephrin deficiency via an indirect pathway (i.e., loss of synaptopodin), as shown in other albuminuric model (19). Bacterial wall components-such as LPS and histone-related proteins-are known to elicit proteinuria (1,32,33,35). These studies provide a clue to explain albuminuria occurred in septic patients (6,25,28), or in subjects after Streptococcal infection in children (13), but the molecular basis has not been fully understood.…”
Section: Wt1 Transfer Into Cytoplasm In Septic Kidneymentioning
confidence: 96%
See 3 more Smart Citations
“…explain the nephrin deficiency via an indirect pathway (i.e., loss of synaptopodin), as shown in other albuminuric model (19). Bacterial wall components-such as LPS and histone-related proteins-are known to elicit proteinuria (1,32,33,35). These studies provide a clue to explain albuminuria occurred in septic patients (6,25,28), or in subjects after Streptococcal infection in children (13), but the molecular basis has not been fully understood.…”
Section: Wt1 Transfer Into Cytoplasm In Septic Kidneymentioning
confidence: 96%
“…However, little information is available about the nephrin dynamism during sepsis-induced albuminuria. It is demonstrated that LPS elicits "transient" albuminuria in rodents (1,27,32). However, the mechanisms of reversibility have not been fully elucidated yet.…”
Section: Morphometric Scoresmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted, however, that many of these proteins are not homogeneously expressed by the endothelium but rather are (micro)vascular bed specific. Moreover, the kinetics of disease-induced target epitope expression may spatiotemporally differ between endothelial cell subsets in the diseased sites (13). This could have either an advantageous or a detrimental effect with regard to specificity and/or extent of local accumulation of the drug delivery formulation.…”
Section: Endothelial Heterogeneity and Abnormal Ecs As Therapeutic Tamentioning
confidence: 99%